Simms-Wallach families papers - Simms, Charles, 1755-1819.
Correspondence, legal papers, financial papers, printed material, and other papers of the Simms and Wallach families relating to the late eighteenth and early nineteenth century history of Washington, D.C., and Alexandria, Va. Papers of Charles Simms include an account book recording the sale of items from the estate of George Washington and legal papers concerning Simms's real estate ownership and litigation in the state of Kentucky.
Charles Simms, businessman, and other members of the Simms and Wallach families living in the Washington, D.C., and Alexandria, Va., area.
Collection material in English.
Keywords: Simms, Charles, -- 1755-1819 -- Trials, litigation, etc; Washington, George, -- 1732-1799 -- Estate; Simms family; Wallach family; Real property -- Kentucky; Alexandria (Va.) -- History; Virginia -- History -- 1775-1865.; Washington (D.C.) -- History